Analisis Kompetensi Pedagogik Guru di SDN 37 Pekanbaru: Dengan Fokus Pada Tantangan Yang Dihadapi dan Solusi - Rahmat Yoza Mandela; Sahrial Harun Paturahman; Ade Irma (CV. Kurnia Grup, 2024)
This study aims to analyze the pedagogical competence of teachers at SDN 37 Pekanbaru, focusing On the challenges faced and solutions that can be applied. The methods used 1n this study were field observation and in-depth interviews with teachers and principals. The results of the analysis indicate that the pedagogical competence of teachers still faces various challenges, including a lack of understanding of innovative learning methods, limitations in the use of educational technology, and low student learning motivation. In addition, environmental factors and parental support also play an important role in the learning process. To overcome these challenges, this study recommends several solutions, such as ongoing training for teachers on creative teaching methods, improving technology facilities in schools. and parental involvement programs in children's education. With the implementation of these solutions, it is hoped that the pedagogical competence of teachers can increase, thus having a positive impact on the quality of learning at SDN 37 Pekanbaru.